Changes in energy expenditure and physical activity over 15 years of environmental changes: The Maycoba project - Niclou, Alexandra; Urquidez Romero, Rene; Esparza-Romero, Julián; Lam, Yan Y; Rood, Jennifer; Schulz, Leslie O; Bennett, Peter H; Valencia, Mauro E; Ravussin, Eric (2024)
Objective: This work aimed to parse out the role of changing environments on body composition, total energy expenditure, and physical activity in the Mexican Pima, a population experiencing rapid industrialization. Methods: Using doubly labeled water, we compared energy expenditure and physical activity in a longitudinal cohort of Mexican Pima (n = 26; female: 12) in 1995 and 2010. Body mass and composition were assessed by bioimpedance analysis. To determine the effects of environmental factors on body weight independent of age, we compared the 1995 longitudinal cohort with an age- and sex-matched crosssectional cohort (n = 26) in 2010. Results: Body mass, fat mass, and fat-free mass all significantly increased between 1995 and 2010. Despite a 13% average increase in body weight, weight-adjusted total daily energy expenditure decreased significantly. Measured physical activity levels also decreased between 1995 and 2010, after we adjusted for weight. Conclusions: Our results suggest that the recent industrialization of the Maycoba region in Sonora, Mexico, has contributed to a decrease in physical activity, in turn contributing to weight gain and metabolic disease among the Mexican Pima.